Bone density and calcium and phosphorus content of the giraffe (Giraffa camelopardalis) and African buffalo (Syncerus caffer) skeletons - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2004.